LIABILITY OF EXPEDITION SERVICE COMPANIES FOR LOSSES SUFFERED BY CONSUMERS - Arie Purnomo; Muhamad Akbar Ramadhan; Rendy Maulana (Jurnal Abdisci, 2025)
Abstract Background. Development in science and technology has an impact on making human work easier in an efficient era. One of them is that the existence of this goods delivery service makes it very easy for people to send goods between cities and islands. The problem is if the goods promised within the specified time do not arrive according to the estimated time or experience delays. Losses experienced by consumers are goods received that are defective, destroyed, or lost. In this case, the consumer can file a lawsuit regarding the losses suffered by consumers against the expedition provider in a civil manner regarding consumer protection. Aims. The purpose of this writing is to find out how responsible expedition service companies are for losses experienced by consumers. Methods. By using 2 (two) types of research methods, namely the library research method (Library Research). Refers to data or research materials that have been previously researched related to the topic of discussion. In this research, the normative juridical research method was used, namely by conducting a literature review, studying the provisions of legislation regarding consumer protection. Conclusion. The efforts made by the expedition service to ensure protection for its service users are also subject to the conscience of the people, who abide by the agreement/peace voluntarily, without anyone feeling defeated, because each provides insurance for the goods shipped. Implementation. This shows that the expedition service company has made efforts to implement articles 7 and 19 of the UUPK, 468 Criminal Code, 1366 Criminal Code, and 188 Laws Number 22 of 2009, which stipulates that the company must provide compensation if the consumer's product is damaged at the time of delivery. However, the compensation provided is not complete if it is not accompanied by insurance.